2020
DOI: 10.1002/mame.202000582
|View full text |Cite
|
Sign up to set email alerts
|

Basalt/Polyacrylamide‐Ammonium Polyphosphate Hydrogel Composites for Fire‐Resistant Materials

Abstract: Hydrogels containing a large amount of water are widely used as fire‐resistant materials. However, when exposed to fire, the organic polymer network of gel will burn in a short time as the contained water evaporates. For that, the fire‐retarding ammonium polyphosphate (APP) and woven basalt fibers are introduced in polyacrylamide (PAAm) hydrogels to improve the fire‐resistant performance. Thermo‐gravimetric tests indicating that the APP can prevent gel from decomposition effectively when the content is larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[79][80][81][82][83] Modifying the hydrogel by silica-based materials such as basalt fibers, intumescent flame retardants such as ammonium polyphosphate (APP), gel fire extinction materials such as WG (water glass, sodium silicate) gel, polymer gel, and composite gel can protect the gel network and matrix materials from burning and extending the fire retardancy time are crucial for hydrogel-based fire-retardant materials. [84][85][86][87][88][89]…”
Section: Flame-retardant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[79][80][81][82][83] Modifying the hydrogel by silica-based materials such as basalt fibers, intumescent flame retardants such as ammonium polyphosphate (APP), gel fire extinction materials such as WG (water glass, sodium silicate) gel, polymer gel, and composite gel can protect the gel network and matrix materials from burning and extending the fire retardancy time are crucial for hydrogel-based fire-retardant materials. [84][85][86][87][88][89]…”
Section: Flame-retardant Materialsmentioning
confidence: 99%
“…More examples, for example, PEGbased hydrogels for coal, are also available. 109 Zheng et al 84 added woven basalt fibers as a biobased additive combined with APP (up to 19 wt%) to enhance fire resistance of polyacrylamide hydrogels. The samples were prepared as N,N-methylenebisacrylamide (MBAA) added to the water solution of acrylamide, and also APP added to the mixture, as well as the TEMED used as an accelerator of the polymerization.…”
Section: Hydrogel-based Flame-retardant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-soluble ammonium polyphosphate (APP) is an inorganic polymer (low degree of polymerization, n < 20) with outstanding water solubility, non-toxic, and biodegradability. APP is an important raw material in water-soluble, chelated, and controlled-release fertilizers [24], flame retardants [25,26], emulsifiers, and food additives, and are low cost [27,28]. According to our observation, studies on the introduction of APP into superabsorbent polymer networks are rarely reported, Wang and co-workers have synthesized new semiinterlayer polymer network (semi-IPN) superabsorbent polymers with slow-release fertilizer based on corn straw cellulose polymers (CSC-g-AA/APP, CSC-g-AA/PVA-APP) [29], and millet straw-based polymer (MSPg-AA/PVA-APP) [30], prepared by solution polymerization has very good adsorption capacity in distilled water, helping to enhance soil water holding capacity and slow release of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium polyphosphate (APP), ammonium dihydrogen phosphate (ADP), ammonium hydrogen phosphate and other phosphorus-based flame retardants are widely used in the field of flame-retarded hydrogels to protect the hydrogel from burning [7]. Zheng et al introduced basalt fibers and ammonium polyphosphate (APP) into polyacrylamide hydrogels to improve the fire resistance properties and found that APP can effectively delay the thermal decomposition process of the hydrogel by forming an expanded char layer [8]. Chen et al introduced modified ammonium polyphosphate into sodium alginate/poly(acrylamide-stearyl methacrylate copolymer) hydrogels to improve the thermal stability and fire resistance of the hydrogels [9].…”
Section: Introductionmentioning
confidence: 99%